Enhancement of Mitochondrial Function by the Neurogenic Molecule NSI-189 Accompanies Reversal of Peripheral Neuropathy and Memory Impairment in a Rat Model of Type 2 Diabetes. (4th July 2022) - Jolivalt, C. G.; Aghanoori, M. R.; Navarro-Diaz, M. C.; Han, M. M.; Sanchez, G.; Guernsey, L.; Quach, D.; Johe, K.; Fernyhough, P.; Calcutt, N. A.
Abstract : Aims . Mitochondrial dysfunction contributes to many forms of peripheral and central nervous system degeneration. Therapies that protect mitochondrial number and function have the potential to impact the progression of conditions such as diabetic neuropathy. We therefore assessed indices of mitochondrial function in dorsal root ganglia (DRG) and brain cortex of the Zucker diabetic fatty (ZDF) rat model of type 2 diabetes and tested the therapeutic impact of a neurogenic compound, NSI-189, on both mitochondrial function and indices of peripheral and central neurological dysfunction. Materials and Methods . ZDF rats were maintained for 16 weeks of untreated diabetes before the start of oral treatment with NSI-189 for an additional 16 weeks. Nerve conduction velocity, sensitivity to tactile and thermal stimuli, and behavioral assays of cognitive function were assessed monthly. AMP-activated protein kinase (AMPK) phosphorylation, mitochondrial protein levels, and respiratory complex activities were assessed in the DRG and brain cortex after 16 weeks of treatment with NSI-189. Results . Treatment with NSI-189 selectively elevated the expression of protein subunits of complexes III and V and activities of respiratory complexes I and IV in the brain cortex, and this was accompanied by amelioration of impaired memory function and plasticity. In the sensory ganglia of ZDF rats, loss of AMPK activity was ameliorated by NSI-189, and this was accompanied by reversal of multiple indices of peripheral neuropathy. Conclusions . Efficacy of NSI-189 against dysfunction of the CNS and PNS function in type 2 diabetic rats was accompanied by improvement of mitochondrial function. NSI-189 exhibited actions at different levels of mitochondrial regulation in central and peripheral tissues.